Chronic Heart Failure In Post-Covid Syndrome (Eurasian Medical Research Periodical, 2023)
In addition to damage to the nervous and respiratory systems, kidneys, liver and other organs, doctors note frequent complications after coronovirus on the heart and blood vessels, which can significantly limit a person’s daily and professional life, as well as cause delayed mortality. There is a sufficient number of studies proving that coronavirus causes complications in the human heart and blood vessels, and such complications also affect patients who have not previously suffered from diseases of the cardiovascular system